Uma nova metodologia de projeto para otimização do volume do converosr boost PFC - Sartori, Hamiltom Confortin (2009)
This work investigates the influence of operation point (Δi @ fs) in the final volume of PFC boost converter. The boost inductor, EMI filter and thermal heatsink are the elements which main influences in the converter volume. These elements are strongly influenced by the chosen operation point, showing a direct relationship among them. With the increase of switch frequency and of the input current ripple occurs reduction of the boost inductor volume. On the other hand, it increases the switching losses in semiconductors, and influence on the EMI filter volume. It should be highlight that the optimum designs of individual devices or parameters of a system could not take the optimization of the overall system. In this form it is strongly recommended that the engineers and designers take into account the overall system, as well available technologies, standard and recommendation, and finally market commitments. The methodology presented realize the converter design in a integrate form, selecting the operation point that the converter finds the minimal total volume, starting from input variable output power, input and output voltage. The design takes into account different semiconductors technologies, different input filter topologies, different heart sinks profile, different magnetic cores technologies further of international standards that the converter must be adapt. Based on an integrate design of converter parameters is possible optimize the design finding the operation point for the minimal volume.